If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4(9) = -19 Multiply -4 * 9 3x + -36 = -19 Reorder the terms: -36 + 3x = -19 Solving -36 + 3x = -19 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + 3x = -19 + 36 Combine like terms: -36 + 36 = 0 0 + 3x = -19 + 36 3x = -19 + 36 Combine like terms: -19 + 36 = 17 3x = 17 Divide each side by '3'. x = 5.666666667 Simplifying x = 5.666666667
| 2p+7q-6(2p-9q+2r)= | | y=4(16)+45 | | 12.6-1x=2x | | 34+y=47+29 | | 3(w+7)+5w=-13 | | 16=4x+45 | | 26.25=2.75x-15 | | 132+8x=16x-12 | | 8n-12=9 | | 7(u+7)+7u=-21 | | 5-6k=8 | | 16-4(3-x)=184 | | 7(u+7)+7u=-17 | | 27-2b=-6 | | 5(x+3)-4=11 | | 6[x+3]+38=2 | | -1-4x=-3-5x | | 8+5[s-1]=18 | | 10x-9=2x+39 | | -3+5v=-13 | | 3x-23=1-(x-4) | | 8(x+13)=24 | | (4*w-6)+2*w=180 | | -9+5n=6n-4 | | 4x^2+18=58 | | 2[r-3]+6=14 | | 27x^3+9x^2-150=0 | | -18=3y+3 | | (2-k)-3(4k+2)= | | 300=75+1.25x | | 3-10b=26+9 | | 6-3y=3x |